TREM1 Regulates Neuroinflammatory Injury by Modulate Proinflammatory Subtype Transition of Microglia and Formation of Neutrophil Extracellular Traps via Interaction With SYK in Experimental Subarachnoid Hemorrhage - Wu, Xinyan; Zeng, Hanhai; Xu, Chaoran; Chen, Huaijun; Fan, Linfeng; Zhou, Hang; Yu, Qian; Fu, Xiongjie; Peng, Yucong; Yan, Feng; Yu, Xiaobo; Chen, Gao (Frontiers in Immunology, 2021)
Neuroinflammation is a key process in the pathogenesis of subarachnoid hemorrhage (SAH) and contributes to poor outcome in patients. The purpose of this study is to explore the effect of triggering receptor expressed on myeloid cells 1 (TREM1) in the SAH, as well as its potential mechanism. In our study, plasma levels of soluble TREM1 was increased significantly after SAH and correlated to SAH severity and serum C-reactiveprotein. TREM1 inhibitory peptide LP17 alleviated the neurological deficits, attenuated brain water content, and reduced neuronal damage after SAH. Meanwhile, TREM1 inhibitory peptide decreased neuroinflammation (evidenced by the decreased levels of markers including IL-6, IL-1β, TNF-α) by attenuating proinflammatory subtype transition of microglia (evidenced by the decreased levels of markers including CD68, CD16, CD86) and decreasing the formation of neutrophil extracellular traps (evidenced by the decreased levels of markers including CitH3, MPO, and NE). Further mechanistic study identified that TREM1 can activate downstream proinflammatory pathways through interacting with spleen tyrosine kinase (SYK). In conclusion, inhibition of TREM1 alleviates neuroinflammation by attenuating proinflammatory subtype transition of microglia and decreasing the formation of neutrophil extracellular traps through interacting with SYK after SAH. TREM1 may be a a promising therapeutic target for SAH.